Thermal Resistance Model of a Flat Plate Solar Air Collector for Energy Efficiency Prediction. Issue 1 (December 2021) - Ong, K. S.; Gobi, K.; Lim, C. H.; Naghavi, S.; Baljit, S.
Abstract: The temperature of a PV panel rises during operation which affects its power output. A PV panel is similar to a flat plate solar collector. This paper presents a simple theoretical heat transfer resistance model and a solution procedure to predict the absorber plate surface temperature of the solar collector. The model consisted of a rectangular cross-section steel duct placed inclined at an angle to the horizontal and exposed to solar radiation. The heat absorbed on the top surface of the plate is transmitted by conduction through the plate and heats the air in the duct. This creates a natural buoyancy effect which induces a natural convection air flow rate. A simple one-dimensional theoretical model of the solar collector with the thermal resistances of the various components is proposed. Simulated results of plate temperature and induced air flow velocity are presented.